Androgen Receptor Promotes Abdominal Aortic Aneurysm Development via Modulating Inflammatory Interleukin-1α and Transforming Growth Factor-β1 Expression. Issue 4 (October 2015) - Huang, Chiung-Kuei; Luo, Jie; Lai, Kuo-Pao; Wang, Ronghao; Pang, Haiyan; Chang, Eugene; Yan, Chen; Sparks, Janet; Lee, Soo Ok; Cho, Joshua; Chang, Chawnshang
<x xml:space="preserve">Abstract</x> Sex difference is a risk factor for abdominal aortic aneurysm (AAA) formation yet the reason for male predominance remains unclear. Androgen and the androgen receptor (AR) influence the male sex difference, indicating that AR signaling may affect AAA development. Using angiotensin II–induced AAA in apolipoprotein E null mouse models (82.4% AAA incidence), we found that mice lacking AR failed to develop AAA and aorta had dramatically reduced macrophages infiltration and intact elastic fibers. These findings suggested that AR expression in endothelial cells, macrophages, or smooth muscle cells might play a role in AAA development. Selective knockout of AR in each of these cell types further demonstrated that mice lacking AR in macrophages (20% AAA incidence) or smooth muscle cells (12.5% AAA incidence) but not in endothelial cells (71.4% AAA incidence) had suppressed AAA development. Mechanism dissection showed that AR functioned through modulation of interleukin-1α (IL-1α) and transforming growth factor-β1 signals and by targeting AR with the AR degradation enhancer ASC-J9 led to significant suppression of AAA development. These results demonstrate the underlying mechanism by which AR influences AAA development is through IL-1α and transforming growth factor-β1, and provides a potential new therapy to suppress/prevent AAA by targeting AR with ASC-J9.